2016
DOI: 10.1016/j.bandc.2016.07.009
|View full text |Cite
|
Sign up to set email alerts
|

The aging brain: Movement speed and spatial control

Abstract: During this aiming task, healthy older adults were less likely than younger adults to sacrifice accuracy for speed. Thus, at least in part, their slowing may be a learned adaptive strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
0
14
1
Order By: Relevance
“…Bradykinesia is characteristic in a spectrum of neurological diseases such as Parkinson’s disease, but is also a hallmark of normal aging. Nonetheless, slowness associated with impaired accuracy more likely represents a pathological condition [ 42 ], such as MHE, where ammonia and other endogenous substances (resulting from an impaired hepatic metabolism) affect brain structure and functionality [ 43 ], causing a bradykinetic pattern like in Parkinson’s disease [ 44 ]. These findings support the results of other studies related to the slowness and inaccuracy demonstrated through the Line Tracing Test and Continuous Reaction Time Test [ 40 , 45 ], and raises the alteration of motor control in patients with MHE prior to physical frailty.…”
Section: Discussionmentioning
confidence: 99%
“…Bradykinesia is characteristic in a spectrum of neurological diseases such as Parkinson’s disease, but is also a hallmark of normal aging. Nonetheless, slowness associated with impaired accuracy more likely represents a pathological condition [ 42 ], such as MHE, where ammonia and other endogenous substances (resulting from an impaired hepatic metabolism) affect brain structure and functionality [ 43 ], causing a bradykinetic pattern like in Parkinson’s disease [ 44 ]. These findings support the results of other studies related to the slowness and inaccuracy demonstrated through the Line Tracing Test and Continuous Reaction Time Test [ 40 , 45 ], and raises the alteration of motor control in patients with MHE prior to physical frailty.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this aspect of performance was notably different from young children. Concurrent with Lamb et al (2016), who had participants make alternating pen marks between a card located at the midline and a number of empty circles on a page, older adults were slower, but more accurate, compared to young adults. Related work with this age group has noted a tendency to sacrifice speed in order to ensure accuracy (Seidler et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Rather, the greater accuracy of older individuals could be due to a shift in speed-accuracy tradeoff (Lamb et al, 2016): older subjects might have favored accuracy over speed. That is, they might have responded more carefully, slowing down their responses to cope better with conflict, as already proposed in the past (Wild-Wall et al, 2008; Verhaeghen, 2011; Hsieh and Fang, 2012; Hsieh et al, 2012).…”
Section: Discussionmentioning
confidence: 99%